Urgensi Penyelesaian Hubungan Industrial Melalui Perundingan Bipartit - Yudin Yunus; Rahmawati; Siti Alfisyahrin Lasori; Albert Pede; Haritsa; Safrin Salam (UNIVERSITAS PGRI YOGYAKARTA, 2023)
Abstract Bilateral negotiations are the first attempt to solve industrial relations problems. It is interesting to study in detail the urgency of bilateral negotiations to resolve industrial relations disputes and the existence of PKB as the legal basis for implementing bilateral PKB. The research method used by the author is normative legal research, which aims to find legal principles, principles and doctrines to answer legal questions. The results of the study show that bilateral negotiations as an initial effort to resolve industrial relations disputes require a commitment of good faith in the negotiation process, collective bargaining and enforcement of collective bargaining. Prudence and prudence are also required in drafting collective labor agreements so that contract clauses do not cause losses or problems in enforcement. Keywords: Urgency. Industrial Relations, Bipartite Negotiations